2018
DOI: 10.1111/gcb.14398
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shifts in distribution and high‐latitude persistence of oceanographic habitat revealed using citizen science data from a climate change hotspot

Abstract: The environmental effects of climate change are predicted to cause distribution shifts in many marine taxa, yet data are often difficult to collect. Quantifying and monitoring species' suitable environmental habitats is a pragmatic approach for assessing changes in species distributions but is underdeveloped for quantifying climate change induced range shifts in marine systems. Specifically, habitat predictions present opportunities for quantifying spatiotemporal distribution changes while accounting for sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 95 publications
(212 reference statements)
1
66
0
Order By: Relevance
“…For many species, migration patterns are tied to prevailing currents, and the duration that preferred environmental conditions are present in particular regions can facilitate or hinder the movements of many pelagic and coastal species that are fished recreationally (Briscoe et al, ). Yellowtail kingfish ( Seriola lalandi, Carangidae) for example is a species caught in eastern Australian fisheries, where the recreational catch exceeds that of the commercial catch (Lowry, Molony, Keag, & Penney, ), and where the distribution of oceanographic habitat has rapidly shifted poleward over the past 20 years (Champion, Hobday, Tracey, & Pecl, ). In the south‐east region of Australia, several “new” highly prized recreational species have been recorded, including mahi mahi or dolphin fish ( Coryphaena hippurus, Coryphaenidae), yellowtail kingfish, snapper and others, creating some excitement among recreational fishers ().…”
Section: Distribution Shiftsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many species, migration patterns are tied to prevailing currents, and the duration that preferred environmental conditions are present in particular regions can facilitate or hinder the movements of many pelagic and coastal species that are fished recreationally (Briscoe et al, ). Yellowtail kingfish ( Seriola lalandi, Carangidae) for example is a species caught in eastern Australian fisheries, where the recreational catch exceeds that of the commercial catch (Lowry, Molony, Keag, & Penney, ), and where the distribution of oceanographic habitat has rapidly shifted poleward over the past 20 years (Champion, Hobday, Tracey, & Pecl, ). In the south‐east region of Australia, several “new” highly prized recreational species have been recorded, including mahi mahi or dolphin fish ( Coryphaena hippurus, Coryphaenidae), yellowtail kingfish, snapper and others, creating some excitement among recreational fishers ().…”
Section: Distribution Shiftsmentioning
confidence: 99%
“…Since the increase in yellowtail kingfish numbers in southern Australia, local charter operators in Tasmania have started advertising for fishing trips (Pecl et al, ). The poleward range extension of yellowtail kingfish (Champion, Hobday, Tracey, et al, ; Robinson et al, ) means that fishers and managers will need to adapt to these changes in future. Marine resource users require information relevant to their activities at decision‐making timescales in order to adapt effectively.…”
Section: Costs Participation and Motivationmentioning
confidence: 99%
“…This species is targeted in several eastern Australian fisheries, where the estimated annual recreational catch exceeds the average annual commercial catch (Henry & Lyle, ; Lowry, Molony, Keag, & Penney, ). Recent analyses have revealed that the distribution of oceanographic habitat for kingfish from eastern Australia has rapidly shifted poleward over the past 20 years (Champion, Hobday, Tracey, et al, ). These analyses are supported by photo‐verified observations of kingfish poleward of their historic southern Australian range boundary recorded by the Range Extension Database and Mapping Project (Redmap; http://www.redmap.org.au; Pecl, Stuart‐Smith, et al, ) and a rapid assessment of species that are likely to be undergoing poleward range extensions in south‐eastern Australia (Robinson, Gledhill, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…These occurrence records were combined with 20,000 pseudo‐absence points randomly generated throughout the study area to categorize unsuitable environmental habitat for kingfish, thus providing a binomial response variable for statistical modelling. Twenty thousand pseudo‐absences were selected to (a) ensure that environmental variability occurring over the spatiotemporal extent encompassed by the occurrence dataset was adequately captured, (b) comply with Barbet‐Massin, Jiguet, Albert, and Thuiller () who recommend selecting a large number (i.e.> 10,000) of pseudo‐absences when using regression techniques to develop species distribution models, and (c) facilitate comparisons with habitat suitability models for other pelagic fishes from eastern Australia (see Champion, Hobday, Tracey, et al, ) that were also developed using approximately 20,000 pseudo‐absences (e.g. Brodie et al () and Hill et al () who used 20,000 and 23,242 pseudo‐absences, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation